Global Methylation Patterns and Their Relationship with Gene Expression and Small RNA in Rice Lines with Different Ploidy - Zhang, Hong-Yu; Zhao, Hui-Xia; Wu, Shao-Hua; Huang, Fang; Wu, Kai-Ting; Zeng, Xiu-Feng; Chen, Xiao-Qiong; Xu, Pei-Zhou; Wu, Xian-Jun (Frontiers in Plant Science, 2016)
Whole genome duplication (WGD) is a major force in angiosperm evolution. Whether WGD is accompanied by the evolution of epigenetic regulators remains to be explored. Here we investigate whole genome methylation, gene expression andmiRNAregulation among monoploid,diploid and triploid rice plants isolated from a twin-seedling population. The DNA methylation patterns in the three different ploidy plants were highly similar, with DNA methylation primarily enriched in the promoters. We examined the methylation of single genes and detected around 25,500 methylated genes, of which 22,751were methylated in all three lines. Significantly divergent DNA methylation patterns between each pair of threelines were only detected in64 genes, though more genes were found to exhibit differential expression. Analysis of DNA methylation and expression patterns showed thathigher DNA methylation levels upstream of the transcription start sites arecorrelated with higher levels of expression of related genes; whereashigher DNA methylation levels in gene body regions arecorrelated with lower levels of expression.We also carried out high-throughputsequencing of small RNA libraries and identified 36 new miRNAs. These miRNAs have differentexpression levels depending on the ploidy.